Transcriptomic profiling of lung alveolar macrophages reveals distinct contribution of sterol metabolism in macrophage response to Cryptococcus gattii infection - Siranart Jeerawattanawart; Adithap Hansakon; Rudi Alberts; Yongliang Zhang; Pornpimon Angkasekwinai (PLoS ONE, 2025)
Alveolar macrophages are well known as the first responders to pulmonary cryptococcosis; however, their dynamic molecular responses to Cryptococcus gattii infection in vivo remain limited. Here, we investigated the transcriptional profiles of lung alveolar macrophages purified from mice intranasally infected with C. gattii and compared them to those infected with C. neoformans using RNA sequencing analysis. Alveolar macrophages from C. gattii-infected mice exhibited distinct transcriptional alterations, particularly in genes associated with sterol biosynthesis, whereas those from C. neoformans-infected mice showed enrichment in interferon and cytokine signaling pathways. Treatment with the sterol biosynthesis inhibitor lovastatin significantly reduced cholesterol accumulation in C. gattii-infected RAW 264.7 cells. Furthermore, lovastatin treatment of C. gattii-infected RAW 264.7 and bone marrow-derived macrophages suppressed intracellular cryptococcal proliferation and augmented inflammatory response, as evidenced by increased expression of Nos2 and Il6. Lovastatin also potentiated the antifungal effect of fluconazole by promoting intracellular fungal clearance and increasing nitric oxide activity in macrophages. In C. gattii-infected mice, lovastatin treatment enhanced the efficacy of fluconazole, resulting in improved pulmonary fungal clearance, increased lung CD4 ⁺ T cell numbers, and elevated nitric oxide activity. Collectively, these findings reveal a unique macrophage response to C. gattii infection and highlight the role of sterol metabolism in modulating host defense, offering potential avenues for therapeutic intervention.